Applied Regression Modelling to Perfect Labor Law Policies Contributed to Increasing the Efficiency of Human Resource Management at FDI Enterprises - Nga, Tran Thi Bich (Bright Publisher, 2024)
Vietnam is an attractive destination for foreign investors thanks to its stable political environment, strategic geographical location, and abundant labor force. However, to maintain and enhance its attractiveness in the eyes of investors, Vietnam needs to pay special attention to attracting and retaining high-quality human resources, especially in foreign direct investment (FDI) enterprises in Vietnam. Therefore, the research objective explores the critical determinants of employee motivation and loyalty. Besides, the research applies both qualitative and quantitative methods. Qualitative research was conducted with 15 business managers with extensive experience in human resource management to explore the factors affecting employee motivation and loyalty. The study used an official questionnaire to survey research subjects and was conducted on an official data set of 800 employees. Still, it was 785 processed and using SPSS 20.0 and Amos software to test the reliability of the scales using Cronbach's alpha reliability coefficient, exploratory factor analysis, confirmatory factor analysis, and structural modelling model (SEM). The structural equation model results showed that five key factors positively influence employees' job motivation and loyalty at FDI enterprises in Vietnam. In addition, the finding that job motivation also affects employees' loyalty with a significance level of 5%. Unique contribution of this study is beneficial in both theory and practice in managerial implications for business leaders to improve human resource management efficiency by using policies to stimulate and motivate employees. The critical recommendation proposes legal policy implications for enhancing employees' job motivation and loyalty for developing and implementing policies to attract high-quality human resources for FDI enterprises.